2019
DOI: 10.1371/journal.pmed.1002978
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health in relation to firearm-related homicides in the United States: A nationwide multilevel cross-sectional study

Abstract: BackgroundGun violence has shortened the average life expectancy of Americans, and better knowledge about the root causes of gun violence is crucial to its prevention. While some empirical evidence exists regarding the impacts of social and economic factors on violence and firearm homicide rates, to the author’s knowledge, there has yet to be a comprehensive and comparative lagged, multilevel investigation of major social determinants of health in relation to firearm homicides and mass shootings.Methods and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 71 publications
1
64
0
2
Order By: Relevance
“…While this mapping project showed spatial and temporal variability in homicides, it is clear that Sandtown‐Winchester and other heavily impacted neighborhoods were already blighted with poverty, crime, vacant properties, and unemployment (16). Studies have shown spatial clustering of homicides to be associated with higher rates of segregation, poverty, and economic disparity (17,18). Another study found that historic crime data and demographic data reflecting poverty were best able to predict future violent crime (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this mapping project showed spatial and temporal variability in homicides, it is clear that Sandtown‐Winchester and other heavily impacted neighborhoods were already blighted with poverty, crime, vacant properties, and unemployment (16). Studies have shown spatial clustering of homicides to be associated with higher rates of segregation, poverty, and economic disparity (17,18). Another study found that historic crime data and demographic data reflecting poverty were best able to predict future violent crime (19).…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach emphasizing collaboration with the DEA allowed for early recognition of the recent fentanyl epidemic in Maryland and timely implementation of public health interventions (22). Although several studies have evaluated crime outcomes using mapping techniques (18,19,21,23,24), the current study highlights how the effects of a unique societal sentinel event such as the death of Freddie Gray are particularly well suited to in‐depth analysis by GIS.…”
Section: Discussionmentioning
confidence: 99%
“…We use the term 'injuries' to include both nonfatal injuries and deaths. GVA data have been used for research on legal intervention shootings, 17 firearm homicides, 18 mass shootings, 19,20 and community violence 21 and have performed well relative to other sources. 17,19 We developed a directed acyclic graph to identify a minimum set of time-varying covariates needed to control for confounding ( Supplementary Figure 1).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Furthermore, an addiction model that motivates carceral investment would detract from funding to redress structural failures that are empirically linked to high rates of violence — including inadequate social spending, low social mobility, residential segregation, and failing public infrastructure. 17…”
Section: Risks Of Medicalizing Violencementioning
confidence: 99%